Association between Related Purine Metabolites and Diabetic Retinopathy in Type 2 Diabetic Patients. (13th February 2014) - Xia, Jianfei; Wang, Zonghua; Zhang, Feifei
Abstract : Aims . The purpose of the study was to investigate the differences of adenosine, adenine, inosine, xanthine, hypoxanthine, and uric acid concentrations in patients with type 2 diabetes mellitus and diabetic retinopathy and assess the relationship between purine metabolites and disease. Materials and Methods . The study group consisted of 114 subjects which were divided into three groups: control (n = 40 ), type 2 diabetes without retinopathy (n = 35 ), and type 2 diabetes with retinopathy (n = 39 ). Levels of metabolites were measured in plasma of all participants. Results . There is a significant increase of levels of adenosine (0.94 ± 0.17 mg/L versus 0.17 ± 0.01 mg/L, P < 0.001 ), inosine (0.297 ± 0.078 mg/L versus 0.086 ± 0.010 mg/L, P < 0.001 ), xanthine (1.01 ± 0.21 mg/L versus 0.54 ± 0.05 mg/L, P = 0.009 ), and uric acid (70.55 ± 3.97 mg/L versus 53.81 ± 2.36 mg/L, P < 0.001 ) with diabetic retinopathy compared to diabetes mellitus. The levels of adenine, hypoxanthine, and xanthine oxidase did not change. Uric acid, xanthine, inosine, and adenosine correlated positively with systolic blood pressure and urea nitrogen. Conclusions . The levels of adenosine, inosine, uric acid, and xanthine may be useful for monitoring the progression of diabetic retinopathy and evaluating the treatment.